Otomastoiditis caused by Sphingomonas paucimobilis: case report and literature review - Gabriel Nuncio Benevides; Noely Hein; Denise Swei Lo; Angela Esposito Ferronato; Selma Lopes Betta Ragazzi; Cristina Ryoka Miyao Yoshioka; Maki Hirose; Debora Morais Cardoso; Silvia Regina dos Santos; Alfredo Elias Gilio (University of São Paulo, 2014)
Sphingomonas paucimobilis is an aerobic Gram-negative bacillus that, although rare in humans, most commonly infects immunocompromised and hospitalized patients. Among the 59 pediatric cases of S. paucimobilis infection reported in the literature, the most common diagnosis involves isolated bacteremia. These cases are related to sporadic or epidemic infections. Death related to this infection occurred in only one case. The authors report a case of an 11-year-old boy with the diagnosis of Sphingomonas paucimobilis otomastoiditis and a thorough review of the literature on this infection in pediatrics. The patient presented a 20-day history of fever, otalgia, otorrhea, and progressive retroauricular swelling with protrusion of the left ear; despite 15 days of amoxicillin regimen. His past medical history included chronic bilateral otitis media, but no cause of immunosuppression was found. A brain computed tomography scan showed left otomastoiditisassociated with a large circumscribed fluid collection with deep involvement of the soft tissues of the temporal region, including the subperiosteal space. Blood tests showed neutrophilia and elevated C-reactive protein. Surgical manipulation of the cited collection drained a large amount of a fetid purulent secretion. Ceftazidime and clindamycin were empirically initiated. The outcome was favorable, with fever defervescence and resolution of the scalp deformation. Culture of the drained secretion was positive for S. paucimobilis. Ciprofloxacin was scheduled for a further 10 days after discharge. The follow-up showed complete recovery. As far as we know, this is the first case of S. paucimobilis otomastoiditis, complicated with subperiosteal abscess in an immunocompetent child. The authors call attention to the increasing number of reports on S. paucimobilis infection over the years, and therefore to the importance of this pathogen, which was previously underestimated.